Combined modalities for the rapid diagnosis of patients with suspected tuberculous lymphadenitis: A cross-sectional study - Mohsin Hasan Sayed; Kavita Sane (Lung India)
Background In settings with high burden of extrapulmonary tuberculosis, the use of various diagnostic modalities can result in superior and quick diagnosis leading to prompt initiation of treatment. Objective This study assessed the diagnostic performance of the fine-needle aspiration cytology (FNAC), Ziehl–Neelsen (ZN) stain, fluorescence microscopy (FM) and cartridge-based nucleic acid amplification test (CBNAAT) in patients with suspected tuberculous lymphadenitis (TBLN). Methods This cross-sectional studyodes, who underwent FNAC. The FNAC samples were subjected to cytomorphological examinati involved 255 patients clinically suspected of TBLN with palpable lymph non, ZN stain, FM and CBNAAT. The diagnostic performance of each modality was compared with CBNAAT, and combined performance was determined. The diagnostic performance of CBNAAT was determined by comparing it with composite reference standard. Results Of 255 patients, 148 (58.04%) showed features of TBLN on FNAC. The presence of epithelioid cell granulomas with caseous necrosis (67.57%) was the predominant cytomorphological pattern. On ZN stain, FM and CBNAAT, 31 (20.95%), 63 (42.57%) and 100 (67.57%) patients were found to be positive for TBLN, respectively. The sensitivity, specificity, positive predictive value and negative predictive value of CBNAAT was 58.59%, 91.83%, 92% and 58.06%, respectively. Finally, the combination of ZN stain, FM and CBNAAT led to the detection of 88.51% patients with TBLN. Conclusion Combined use of ZN stain, FM and CBNAAT leads to superior and swift diagnosis of patients with clinically suspected TBLN.